Peran Guru Dalam Manajemen Kelas Komprehensif Di Sekolah Dasar Al-Baitul Amien 02 Full Day School Jember - Fajar Abdillah (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2020)
Abstract: Students spend most of their time in the classroom. It is therefore not surprising that students feel joy and feel happy when the bell breaks ring. Not to mention the students also need time to play and time to rest his brain. The primary school of al-Baitul Amien jember is a school that implements a full day learning system. If it refers to the reason for the misfortune, depriving the physical and psychological time to play and tired is of course the number of students will decrease, because the guardians do not want their children to experience physical or psychological exhaustion. But the reality on the ground shows that this school more and more demand even now there are two school complex. The students feel enjoy it even though they spend time in class. Therefore, it would be interesting if further explore how the role of teachers in managing the class so that students still enjoy even all day at school. Keywords: Teacher Role, Comprehensive Classroom Management